Analysis Of Religious Moderation Policy Within The Framework Of Islamic Education In Indonesia: A Documentary Study - Armedi, Rama; Rudini; Hafidz Imaduddin (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Intolerance and radicalism remain serious challenges to diversity in Indonesia, where schools which should serve as pillars of democracy have not yet been fully able to counter these challenges. Although religious moderation has been introduced as a solution, research specifically analysing formal policies as a foundation for integration within Islamic education remains very limited. The aim of this study is to analyse government policies regarding the strengthening of religious moderation through a qualitative approach, utilising a documentary study of Presidential Regulation No. 58 of 2023 and the National Medium-Term Development Plan (RPJPN) 2025–2045. The findings indicate that the strengthening of religious moderation within educational institutions can be implemented through four models: understanding, prevention, eradication, and development. Practical strategies include training for Islamic Education teachers, the development of teaching materials, interfaith activities, and academic publications. This study makes a theoretical contribution by clarifying the position of religious moderation within the national education system, as well as a practical contribution in the form of a structured approach for policymakers in Islamic educational institutions to foster an inclusive national character.